Analysis of Heat Flux Quenching of a Cylindrical Rod Using Oxide Based Nanofluids - Gupta V.; Mishra P.; Mishra D.; Ghosh P. (My University, 2025)
Quenching is an immediate cooling process; however, the jet impingement technique is an efficient method for cooling in constrained space. In the nuclear reactor to prevent the loss of coolant accident condition, DI water is stored in the repository of emergency core cooling system. Nanofluids exhibit better heat removal capacity thus, the present article investigates experimentally an optimum oxide based nanofluid for different mass flow rates from 4 g/s to 9 g/s. Heat flux is increasing up to a limit when the quench front is not able to wet the heater surface, that heat flux is named as Limiting heat flux for that particular cooling condition. Nanofluids are showing better quenching characteristics compared to DI water. Limitation of heat flux is defined with experimental results for every flowing fluid and flow rate condition. Set wall temperature has been taken from 150 to 300 °C. Quench front velocity calculation is the criteria to decide the limiting case. Quenching curves with different fluids at a particular heat flux condition have been recorded at different locations of the heater surface. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.